Pre-hospital care received by injured children less than five years admitted to the Lady Ridgeway Hospital for Children, Colombo - Gayani Gunawardhana; Sampatha Goonewardena (College of Community Physicians of Sri Lanka, 2016)
Objective To describe the pre-hospital care received by injured children less than five years admitted to the Lady Ridgeway Hospital and associated factors. Methods A hospital based descriptive cross sectional study was carried out at the Lady Ridgeway Hospital accident ward. A sample of 400 pairs consisting of a pre-hospital care giver and child were recruited. Structured pre-tested interviewer administered questionnaire was used for data collection and descriptive analysis was used. Results Mean age of the children and pre hospital care giver was 38 months (SD±13.27) and 32.8 years (SD±5.9) respectively. Majority 90.5% (N=362) of care givers were mothers and only 15.7% of had first aid training. However, most (60.5%) of care givers had good knowledge on first aid. First aid box with basic equipment was available for 56.8% injured children. Majority (59.3%) of children was transported within the golden hour and used three wheelers (57%). Although a majority (87.5%) of care givers had access to communication methods only 21.5% knew the emergency telephone number. Conclusions Correct first aid practice was significantly associated with first aid training of the care giver. Since most injured children were transported by three-wheelers, it is imperative to train three-wheeler drivers about how to transport injured children safely.